Transradial access with intra-aortic catheter looping for the treatment of intracranial aneurysms - Xu, Gang-Qin; Ba, Yue-Yang; Cai, Dong-Yang; Yang, Bo-Wen; Zhao, Tong-Yuan; Xue, Jiang-Yu; Li, Tian-Xiao; Gao, Bu-Lang (Frontiers in Neurology, 2023)
Purpose The study aimed to investigate the feasibility and effect of transradial access with intra-aortic catheter looping for the treatment of intracranial aneurysms. Materials and methods This retrospective one-center study was performed on patients with intracranial aneurysms which were embolized through transradial access with intra-aortic catheter looping because of the difficulty of transfemoral access or transradial access without intra-aortic catheter looping. The imaging and clinical data were analyzed. Results A total of 11 patients were enrolled, including seven (63.6%) male patients. Most patients were associated with one or two risk factors of atherosclerosis. There were nine aneurysms in the left internal carotid artery system and two aneurysms in the right internal carotid artery system. All 11 patients had complications with different anatomic variations or vascular diseases, which made endovascular operation via the transfemoral artery difficult or a failure. The right transradial artery approach was adopted in all patients, and the success rate of intra-aortic catheter looping was 100%. Embolization of intracranial aneurysms was successfully completed in all patients. No instability of the guide catheter was encountered. No puncture site complications or surgical-related neurological complications occurred. Conclusion Transradial access with intra-aortic catheter looping for embolization of intracranial aneurysms is technically feasible, safe, and efficient as an important supplementary approach to the routine transfemoral access or transradial access without intra-aortic catheter looping.